Cyanophycean Algae from the Foothills of Indo-Western Himalaya - Shukla, Sunil Kumar; Misra, P. K.; Shukla, Chandra Prakash (Ecoprint: An International Journal of Ecology, 2010)
Twenty six cyanophycean taxa were collected from Pilibheet, Nainital foothills of western Himalayas, belong to 8 genera viz. Chroococcus, Aphanocapsa, Merismopedia, Oscillatoria, Lyngbya, Anabaena, Aulosira and Anabaenopsis. These taxa are represented by 22 species, 3 varieties and 1 forma. All these taxa from Pilibheet are the first report. Key words: Cyanophycean algae, Pilibheet, Nainital. DOI: 10.3126/eco.v16i0.3475 ECOPRINT 16: 65-73, 2009